2011
DOI: 10.1088/0004-637x/745/1/63
|View full text |Cite
|
Sign up to set email alerts
|

Diffusive Acceleration of Particles at Oblique, Relativistic, Magnetohydrodynamic Shocks

Abstract: Diffusive shock acceleration (DSA) at relativistic shocks is expected to be an important acceleration mechanism in a variety of astrophysical objects including extragalactic jets in active galactic nuclei and gamma-ray bursts. These sources remain good candidate sites for the generation of ultrahigh energy cosmic rays. In this paper, key predictions of DSA at relativistic shocks that are germane to the production of relativistic electrons and ions are outlined. The technique employed to identify these characte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
238
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(253 citation statements)
references
References 85 publications
(230 reference statements)
14
238
0
1
Order By: Relevance
“…This is in agreement with numerical simulations of relativistic shocks, which have demonstrated that diffusive shock acceleration forms such power-law spectra (Achterberg et al 2001;Spitkovsky 2008;Summerlin & Baring 2012). Therefore, shocks are frequently used to explain blazar flaring activities.…”
Section: Introductionsupporting
confidence: 89%
“…This is in agreement with numerical simulations of relativistic shocks, which have demonstrated that diffusive shock acceleration forms such power-law spectra (Achterberg et al 2001;Spitkovsky 2008;Summerlin & Baring 2012). Therefore, shocks are frequently used to explain blazar flaring activities.…”
Section: Introductionsupporting
confidence: 89%
“…The same observations are evident as well in the works of e.g. Ellison & Double (2004), Baring (2004), Niemiec & Ostrowski (2004), and Summerlin & Baring (2012). In other words, Monte Carlo simulation studies independently showed that there is an absent "universal" powerlaw spectrum in relativistic shocks, and a variety of spectral indices depending either on shock inclinations, shock speeds, or scattering operators.…”
Section: Single-oblique Relativistic Shock Studiessupporting
confidence: 68%
“…Because we aim to consolidate the understanding of the results that will follow, we recapitulate and discuss here a selection of previous numerical studies based on the MQ03 Monte Carlo code for single relativistic shocks, and compare them with similar studies of Ellison & Double (2004), Niemiec & Ostrowski (2004), Baring (2004), and Summerlin & Baring (2012). As we will see in Sect.…”
Section: Single-oblique Relativistic Shock Studiesmentioning
confidence: 98%
“…Further energization can occur in those cells where the magnetic field is oriented favorably. The TEMZ code very roughly includes this effect by allowing the maximum energy in rest-mass units, γ max , of the electrons to increase by a specified factor (left as a free parameter, with a value of 20 in the current BL Lac simulation) if the magnetic field is oriented nearly parallel to the shock normal-the "subluminal" regime within which some particles can cross the shock multiple times before they are swept downstream with the flow (see, e.g., Summerlin & Baring 2012). This creates an extension to the electron energy distribution at the high-energy end in some of the cells.…”
mentioning
confidence: 99%